2021
DOI: 10.1155/2021/8846869
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Method for Fluid‐Solid Coupling Vibration Analysis of Hydraulic Pipeline System with Hinged Ends

Abstract: The vibrations in hydraulic pipeline systems inevitably involve the interaction between the two-phase media of a solid and fluid. The fluid flowing in the pipeline generates pressure on the pipeline wall and thus causes vibration and deformation in the pipeline, which in turn changes the fluid flow condition, thereby cyclically affecting the deformation and motion of the solid and fluid and making the pipeline system vulnerable to vibration damage. Therefore, it is of great theoretical and practical value to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The direct FSI approach provides an intuitive and accurate method for solving FSI problems by solving the fluid and solid domains simultaneously within a single solver. The control equations for the direct FSI approach are presented as follows [53].…”
Section: The Solution Methods For Fluid-structure Interaction In a Da...mentioning
confidence: 99%
“…The direct FSI approach provides an intuitive and accurate method for solving FSI problems by solving the fluid and solid domains simultaneously within a single solver. The control equations for the direct FSI approach are presented as follows [53].…”
Section: The Solution Methods For Fluid-structure Interaction In a Da...mentioning
confidence: 99%
“…The results indicated that increases in material viscosity decrease the critical flow velocity that can cause pipeline vibration. Zhang and Cui (2021) focused on an aviation hydraulic pipeline and established a fluid-solid coupling vibration model of a pipeline system by considering the effect of the clamp. The validity and accuracy of the vibration model were verified via the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these areas of applications expose them to vibrations and mechanical shocks. For instance, a connector pipe in hydraulic coupling systems incurs hydraulic shock each time a submersible pump is turned-on [37]. Therefore, the study of the damping behaviour of Cu-Zn-Sn based alloys is necessary to evaluate their reliability in service.…”
Section: Introductionmentioning
confidence: 99%